Tadriis al-Nahw Fii Dhaw al-Nadzariyyat al-Ma'rifiyyat li Thullaab al-Shaff al-Raabi' bi Ma'had Daar al-Naja al-Islaamiyy al-Salafiyy Funurughu - Rikza, Muhammad Noval; Mujib, Ahmad (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2019)
The purpose of this study to find out: 1) the appropriateness of learning nahwu with the principles of cognitive theory and 2) the problem of learning nahwu with in the perspective of cognitive theory for 4th grade students at Salaf Boarding School Daarunnajaa Ponorogo. This study uses a descriptive method of analysis with qualitative approach. The results of this study are as follows: 1) Learning nahwu for 4th grade students at Salaf Boarding School Daarunnajaa Ponorogo in accordance with some learning procedures in the cognitive perspective and reflects its realization in the learning process nahwu and also not out or different from some basic procedures include: preparation of the title of the material in textbooks, teachers entering the classroom and greeting the students, the teacher starts the lesson by explaining the rules and then giving examples, the education has a meaningful activity position, the teacher uses an intermediate language, error correction is an integral part of the linguistic activities in the classroom, the learning takes place with one the concept begins with a conscious understanding and ends with training and learning rules. 2) The problem of learning nahwu in the perspective of cognitive theory that includes from the problem of intelligence, attention and memory